A Study of the Purposes of Functioning of a Group of Extensive Livestock Family Farms - Dieguez, Francisco (Agrociencia Uruguay, 2020)
This work presents an analysis of the aims of functioning for some family livestock farmers and the strategic rules to accomplish them. For this task twenty Purposes and Strategic Rules diagrams generated with the Farm Global Approach methodology (AGEA) were used as a way of modeling the property. Multivariate cluster analysis and a network approach were considered to have a whole integrated vision of the results, as tools to generate homogeneous clusters of Purposes of system functioning and its subordinated Strategic Rules. As general hypothesis we establish that there exist some non-economic goals that are determining the functioning way of the family-farm systems. The concepts expressed in the models were grouped by analogy considering the three dimensions of sustainability: economic, social and agro-ecological issues. The results show a high frequency of occurrence for the economic goals related to income and assets, and other non-economic ones, linked to the rural lifestyle. These goals have as common rules ensuring income, risk and costs management, and management of the information. No agro-ecological purposes were found. Knowledge of the purposes of farms and what is done to achieve them seem to be an essential issue to comprehend the way of functioning of the family-farm systems, especially when any technical intervention is planned.